2021
DOI: 10.2217/fon-2021-0302
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Intelligence to Predict 30-day Mortality in Patients with Cancer

Abstract: Aim: An augmented intelligence tool to predict short-term mortality risk among patients with cancer could help identify those in need of actionable interventions or palliative care services. Patients & methods: An algorithm to predict 30-day mortality risk was developed using socioeconomic and clinical data from patients in a large community hematology/oncology practice. Patients were scored weekly; algorithm performance was assessed using dates of death in patients’ electronic health records. Results: For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 31 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Following Plan-Do-Study-Act (PDSA) methodology, 8 we implemented the Jvion Care Optimization and Recommendation Enhancement augmented intelligence (AI) tool, which applied continuous machine learning (ML) to predict risk of preventable harm (avoidable ACU) and generated patient-specific recommendations. [9][10][11][12] At their discretion, nurses contacted at-risk patients with interventions to avert the ACU.…”
Section: Specific Aimmentioning
confidence: 99%
“…Following Plan-Do-Study-Act (PDSA) methodology, 8 we implemented the Jvion Care Optimization and Recommendation Enhancement augmented intelligence (AI) tool, which applied continuous machine learning (ML) to predict risk of preventable harm (avoidable ACU) and generated patient-specific recommendations. [9][10][11][12] At their discretion, nurses contacted at-risk patients with interventions to avert the ACU.…”
Section: Specific Aimmentioning
confidence: 99%
“…We found that the most common use of AI for predictive modeling in SPC was focused on mortality. Many studies in Table 1 and approximately half of all studies included in total focused on predicting mortality as a clinical outcome, which includes predicting short-term mortality risk 14▪,15,18▪,24▪ and survival over a longer horizon 19–21,22▪▪,23▪▪,25,29. Mortality risk and survival time were both usually predicted using machine learning (ML) models that analyze various patient factors such as clinical parameters, changes during treatment, and symptoms 14▪,15,18▪,20,21,22▪▪,23▪▪,24▪,25.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of ML and deep learning (DL) models is typically evaluated by their area under the curve (AUC) value, which measures the accuracy of predictions and a model’s discriminative ability where 1.0 represents the highest possible AUC score indicating perfect discrimination 11,39. The models in Table 1 had AUC values between 0.70 and 0.92 indicating generally good model performance 14▪,15,18▪,19–21,23▪▪,24▪,25,26,40. Interestingly, models predicting 60-day and especially 180-day mortality had lower AUC values compared to 30-day mortality models 19,20,24▪,40, suggesting that predicting acute mortality risk could be more reliable than prediction over a longer term.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations